Influence of BIM (Building Information Modeling) Technology on Construction Efficiency - Mohamad Djaelani (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Building Information Modeling (BIM) represents a groundbreaking technology that has reshaped the construction sector by offering more streamlined and integrated solutions across different project stages, from planning and design to facility management and maintenance. As a digital system, BIM enables construction experts to engage with precise and integrated data through 3D models, which merge both technical and functional characteristics of the building. This article explores how BIM impacts construction efficiency, particularly in terms of time, cost, quality, and team coordination. Research and case studies indicate that BIM significantly improves construction processes by minimizing waste, accelerating timelines, and enhancing the effectiveness of facility upkeep.